Computational modeling and experimental data collection for Salmonella Enteritidis PT 30 cross-contamination and dry cleaning interventions in milk powder production environments: A multi-scenario analysis - Jincheng Ma; Yingwen Tang; Shaojin Wang; Byron D. Chaves; Long Chen (Food Microbiology, 2026)

Durable and efficient 2D/3D perovskite bulk heterojunction solar cells via BA2MAPb2I7 single crystal addition - Zihong Cai; Xin Chen; Zixing Guo; Yafei Wang; Tianqi Niu; Junyu Lin; Shihai Ye; Qianqiu Guan; Jiazhen Xu; Jiale Huang; Tao Zou; Zuoshan Zhang; et al. (Chemical Engineering Journal, 2026)

Impacts of engineering activities on the permafrost environment in the Hola Basin in the Northern Da Xing'anling Mountains in Northeast China - Hongwei Wang; Xiaoying Li; Ruixia He; Juan Zhang; Wenhui Wang; Yuan Qi; Jinlong Zhang; Rui Yang; Yan Li; Xiaoying Jin; Shuai Huang; Jianjun Tang; et al. (Engineering Geology, 2026)

Sedimentary records of silicate weathering on the continental shelf of the South Yellow Sea during glacial periods - Jin Zhang; Shiming Wan; Yifei Yang; Shouye Yang; Peter D. Clift; Yulong Guo; Debo Zhao; Yi Tang; Zhaojie Yu; Zehua Song; Zhongjing Cheng; Zaibao Yang; et al. (Science China Earth Sciences, 2026)

Determinants of physiological demands, physiological resilience, and muscle fatigability during load carriage in women: an observational trial - Erin E. Robertson; Charlotte V. Coombs; Ella B. Halsall; Christina D. Young; Alice S. Irving; Jonathan C. Y. Tang; Julie P. Greeves; Thomas J. O’Leary (European Journal of Applied Physiology, 2026)

Pelagic Sargassum as a sustainable source of food-grade alginate: selective functional modulation by high-pressure processing and sonication - Aravind Kumar Bingi; Yaqi Zhao; Yu-Jou Chou; Chunya Tang; Banghao Chen; Jeremy D. Owens; Brian E. Lapointe; Rachel A. Brewton; Imran Ahmad; Qinchun Rao (Food Hydrocolloids, 2026)

Structural performance of CLT wall-to-foundation connection system in the presence of decay - Kamal Neupane; Hyungsuk Lim; Juliet D. Tang; Minghao Li; Frank Lam; Yunsang Kim (Engineering Structures, 2026)

Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Early-life neighborhood resources and later-life cognitive function - Justin G. Farmer; Ian W. Tang; Peter James; Laura D. Kubzansky; Rajarshi Mukherjee; Ruby Hickman; William Kessler; Laura T. Germine; Marc G. Weisskopf (Environmental Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The impact of digital finance on ecological environment resilience in the Yangtze River Delta region - C. Zhu; C. Duan; D. Ma; Z. Wang; S. Tang (International Journal of Environmental Science and Technology, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Simultaneous photochemical oxidation of As(III) and Mn2+(aq) in the presence of hematite - Junyeong Choi; Donggeun Kim; Seung Soo Steve Lee; John D. Fortner; Yoon Myung; Yuanzhi Tang; Haesung Jung (Water Research, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A new method to improve the detection rate and astrometric accuracy of natural satellites located in the halo of Uranus - Z.Y. Wang; H.Y. Zhang; R.C. Qiao; Y. Yu; D. Yan; K. Tang (Icarus, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Meal Preparation Strategies and Lack of Food Security Among Unaccompanied Latino Migrant Farmworker Youth in Georgia and Florida: A Mixed-Methods Approach - Fiorella L. Carlos Chavez; Kaleea R. Lewis; Bethany A. Moore; Tracy Tang; Edward D. Vargas; Joan M. Hermsen; Rebecca E. Lee; Youngbin Lee; Irma A. Arteaga; Khushi Bypan; J. Sanford Rikoon; Thomas A. Arcury (Journal of Agromedicine, 2026)

Direct nonoxidative methane conversion ceramic membrane reactor with in-situ coke removal - Qiming Tang; Muhammad Saqib; Aniqa Anjum; Keith Duncan; Eric D. Wachsman (Chemical Engineering Journal, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A new entolomatoid species of Rhodophana (Entolomataceae, Agaricales) from Thailand - Lei Lei; Feng-Ming Yu; Song-Ming Tang; Kevin D. Hyde; Thatsanee Luangharn; Qi Zhao (New Zealand Journal of Botany, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Machine learning models for predicting postoperative delirium in non-cardiac surgery patients — systematic review and meta-analysis - Oishika Das; Linda Y. Tang; Esther S. Oh; Jose Suarez; Nicholas Theodore; Tej D. Azad (GeroScience, 2025)

Comparing continuous-corn and soybean-corn rotation cropping systems in the U.S. central Midwest: Trade-offs among crop yield, nutrient losses, and change in soil organic carbon - Ziyi Li; Kaiyu Guan; Wang Zhou; Bin Peng; Emerson D. Nafziger; Robert F. Grant; Zhenong Jin; Jinyun Tang; Andrew J. Margenot; DoKyoung Lee; Carl J. Bernacchi; Evan H. DeLucia; et al. (Agriculture, Ecosystems & Environment, 2025)

Solid-state microwave phase control for improved heating patterns in single-mode cavities - Xu Zhou; Zhongwei Tang; Patrick D. Pedrow; Juming Tang (Innovative Food Science & Emerging Technologies, 2025)

Deep learning assisted denoising of fast polychromatic X-ray micro-CT imaging of multiphase flow in porous media - E.S. Mathew; S.J. Jackson; D. Wildenschild; P. Mostaghimi; K. Tang; R.T. Armstrong (Computers & Geosciences, 2025)

Deadwood Supports Carnivores in Leaf Litter Communities in a Bark Beetle-Attacked Deadwood Simulation Experiment - N. V. Benedetto; J. J. Riggins; J. D. Tang; C. M. Siegert; J. Thomason; N. Dearing; N. A. Clay (Forest Science, 2025)

Periphytic biofilm (PB) in paddy field: A natural cadmium barrier for rice (Oryza sativa L.) safe production through physiological detoxification and gene regulation - Haiying Lu; Lingyuan Chen; Junzhuo Liu; Xianjin Tang; Chen Chen; Mohamed S. Sheteiwy; Jie Yu; Xukui Wang; Jiangang Han; Yonghong Wu; Dionysios D. Dionysiou (Journal of Hazardous Materials, 2025)

Assessing resilience of transit networks: An activity-based space-time accessibility analysis - Yuqing Zhou; Xiao Fu; Tianli Tang; Khoa D. Vo; Eiji Hato (Sustainable Cities and Society, 2025)

Evolution of silicate weathering in the Yangtze River Basin since 3.5 Ma as archived in the East China Seas: Controlling factors and global significance - Jin Zhang; Shiming Wan; Peter D. Clift; Hualong Jin; Zehua Song; Yi Tang; Zhaojie Yu; Kaidi Zhang; Jian Lu; Wenjun Jiao; Anchun Li (Global and Planetary Change, 2025)

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Dynamic environment but no temperature change since the late Paleogene at Lühe Basin (Yunnan, China) - Caitlyn R. Witkowski; Vittoria Lauretano; Alex Farnsworth; Shu-Feng Li; Shi-Hu Li; Jan Peter Mayser; B. David A. Naafs; Jingyi Wei; Robert A. Spicer; Tao Su; He Tang; Zhe-Kun Zhou; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Methane adsorption capacity of shale in the upper Permian Longtan Formation in the eastern Sichuan–northern Guizhou region, South China - X-M. Li; X. Tang; S-B. Guo; Y-S. Shan; E-D. Deng; C-L. Lan; B-D. Tan (Australian Journal of Earth Sciences, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Mapping risks: A value chain approach to brucellosis introduction in Zhijiang's Cattle Population, China - Zihan Tian; Sheng Jiang; Peng Yuan; Xiaozhong Wang; Jie Pei; Hao Tang; Shubo Li; Ian D. Robertson; Aizhen Guo; Yingyu Chen (Preventive Veterinary Medicine, 2025)

Comparative analysis of immunization strategies for broad-specificity antibody preparation and immunoassay development for sulfonamides detection in chicken and pork samples - Xiaoyue Xiao; Zhenzhen Chen; Jiawei Chen; Yanyan Tang; Gan Zhang; Juan Peng; Daofeng Liu; Bruce D. Hammock; Weihua Lai (Food Bioscience, 2025)

Nano-aggregation of asphaltenes and its influence on the multiscale properties of bitumen recycled through multiple ageing and rejuvenation cycles - Yongping Hu; Yike Yin; Anand Sreeram; Jiayao Liu; Wei Si; Dong Tang; Gordon D. Airey (Chemical Engineering Journal, 2025)

The Random RFPA Method for Modelling Rock Failure - Bin Gong; Tao Zhao; Indrasenan Thusyanthan; Chun’an Tang; Gordon G. D. Zhou (Rock Mechanics and Rock Engineering, 2025)
The random rock failure process analysis (RRFPA) method was developed in this research to characterize the material spatial variability and uncertainty in rock failure modelling. The random field theory (RFT) was integrated with the traditional rock failure process analysis (RFPA) to model rock heterogeneity. In this approach, the variation of rock properties is represented as a function of relative distance, such that the influence of material intrinsic correlation on its fracturing behaviour can be appropriately captured. To validate the theory, 300 RRFPA simulations were conducted to investigate the failure characteristics of rock samples under compressive loading. The results showed that by incorporating a spectrum of material properties, the numerical outcomes exhibited distinct upper and lower bounds of stress across all testing scenarios, closely aligning with the experimental relationships. The histograms for uniaxial compressive strength and elastic modulus showed that both properties followed normal distributions, with the average values of 10.099 MPa and 1.818 GPa, respectively. The corresponding coefficients of variation were 0.450 and 0.038. The localized failure tended to result in a more rapid release of acoustic emission energy, but generated smaller cumulative energy compared to the overall failure pattern. In general, the maximum relative error of the RRFPA model was only 0.66% for uniaxial compressive strength, elastic modulus, and critical axial strain.

Influence of soil substrate availability and plant species diversity on soil microbial biomass and enzyme activity in a subalpine natural secondary forest - Tiantian Tang; Zongda D. Hu; Yihao Wang; Jing Hu; Dagang Yuan; Lei Cai; Qiuhong Feng; Zhiyou Wen; Jiujin Xiao (Journal of Soils and Sediments, 2025)

A review on natural sweeteners, sweet taste modulators and bitter masking compounds: structure-activity strategies for the discovery of novel taste molecules - Jin-Pyo An; Yu Wang; Steven D. Munger; Xixuan Tang (Critical Reviews in Food Science and Nutrition, 2025)

Addressing decarbonization strategies through a game theory perspective - Elizabeth A. Moore; Karan Bhuwalka; Andy Zhu; Yijia Chen; Panya Tang; Jennifer D. Russell; Randolph Kirchain; Richard Roth (Resources, Conservation and Recycling, 2025)

A pathway-based genetic score for inflammation: An indicator of vulnerability to phthalate-induced adverse neurodevelopment outcomes - Ahmed Elagali; Alex Eisner; Samuel Tanner; Katherine Drummond; Christos Symeonides; Chloe Love; Mimi LK. Tang; Toby Mansell; David Burgner; Fiona Collier; Peter D. Sly; Martin O'Hely; et al. (International Journal of Hygiene and Environmental Health, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Clioquinol inhibits angiogenesis by promoting VEGFR2 degradation and synergizes with AKT inhibition to suppress triple-negative breast cancer vascularization - Yuan Gu; Tianci Tang; Moqin Qiu; Hongmei Wang; Emmanuel Ampofo; Michael D. Menger; Matthias W. Laschke (Angiogenesis, 2025)
Inhibition of angiogenesis, either as monotherapy or in conjunction with other treatments, holds significant promise in cancer treatment. However, the limited efficacy of clinically approved anti-angiogenic agents underscores the urgent need for the development of novel drugs and therapeutic strategies. In this study, we demonstrate the highly selective inhibitory effects of clioquinol, a topical antifungal and antibiotic agent, on the angiogenic activity of endothelial cells (ECs) in a series of in vitro angiogenesis assays. Moreover, clioquinol effectively suppressed blood vessel formation in ex vivo aortic ring and in vivo Matrigel plug assays. Mechanistic studies revealed that clioquinol directly binds to the ATP-binding site of vascular endothelial growth factor receptor 2 (VEGFR2), promoting its degradation through both proteasome and lysosome pathways. This led to the down-regulation of the downstream extracellular signal-regulated kinase (ERK) pathway. In addition, the combination with the AKT inhibitor MK-2206 synergistically boosted the anti-angiogenic efficacy of clioquinol in vitro and in an in vivo dorsal skinfold chamber model of triple-negative breast cancer (TNBC), leading to the suppression of TNBC growth. Accordingly, clioquinol, either alone or in combination with AKT inhibitors, represents a promising therapeutic agent for future anti-angiogenic cancer treatment.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Integrating RFPA and DEM in Adaptive RDFA Modeling of Rock Fracturing Process - Bin Gong; Tao Zhao; Indrasenan Thusyanthan; Chun’an Tang; Gordon G. D. Zhou (Rock Mechanics and Rock Engineering, 2025)

Mycotoxin concentrations in rice are affected by chalkiness, grain shape, processing type, and grain origin - Erasmus N. Tang; Sali A. Ndindeng; Geoffrey Onaga; Alejandro Ortega-Beltran; Titilayo D. O. Falade; Rousseau Djouaka; Michael Frei (Mycotoxin Research, 2025)
Mycotoxins such as aflatoxins (AFs), fumonisins (FBs), zearalenone (ZEN), and deoxynivalenol (DON) pose a risk to public health due to their carcinogenic potency (AFs and FBs) and anti-nutritional effects. The hazards associated with mycotoxins are accentuated where food management practices, control, and regulatory systems from farm to plate are sub-optimal. Information on the frequency of these mycotoxins in rice commercialized in markets in sub-Sahara Africa (SSA) is limited. The current study examined AF concentrations in 527 rice samples collected from 54 markets in five SSA countries. Grain quality characteristics, processing methods, and origin of samples were contrasted with toxin levels. In total, 72% of the samples had detectable AFs levels (range = 3.0 to 89.8 µg/kg). Forty-seven percent (47%) of the samples had AFs above 4 µg/kg, the European Union maximum level (ML), and were evaluated for cooccurrence with FBs, ZEN, and DON. Total AFs and ZEN cooccurred in 40% of the samples, and 30% of the positive ZEN samples had concentrations above the ML of 75 µg/kg. Total AFs did not co-occur with FBs and DON. Multivariate analysis revealed that length-to-width ratio ( p < 0.0001), mixed variety for width ( p = 0.04), and chalkiness ( p = 0.009) significantly influenced aflatoxin concentrations. Slender grains had higher AFs concentrations than bold and medium grains ( p < 0.0001). Possible strategies to mitigate mycotoxin contamination in rice include improving grain quality traits and practicing proper drying and hermetic storage before and after milling. These findings provide valuable insights for both domestic and international actors in establishing and strengthening regulations and management systems to mitigate rice mycotoxin contamination.

Current progress in the development of biosensors based on nanomaterials for the detection of inorganic arsenic - Y.P. Zheng; W. Li; T.H. Liu; X. Li; Y.F. Tang; D. Zhi; B. Peng; Y.Y. Zhou (International Journal of Environmental Science and Technology, 2025)

Tree populations show low regeneration of valued species in West Africa - Anne Mette Lykke; Nanna Rømer; Patrick Gonzalez; Romain Glèlè Kakaï; Habou Rabiou; Kossi Béssan Amegnaglo; Souleymane Ganaba; Bienvenu Sambou; Fatimata Niang; Bruno Herault; Reginald Tang Guuroh; Paulin Ouoba; et al. (Biological Conservation, 2025)

Investigation on Well Interferences of Infill Well Fracturing in Shale Gas Reservoirs Across Sichuan Basin - Xuanhe Tang; Haixin Yang; Haiyan Zhu; Maurice B. Dusseault; John D. McLennan; Kuidong Li; Jialin Xiao; Bo Zeng; Majia Zheng; Lishi Lin; Wei Liu (Rock Mechanics and Rock Engineering, 2025)

The impact of early life exposure to individual and combined PFAS on learning, memory, and bioaccumulation in C. elegans - Seth D. Currie; Yuqing Ji; Qingguo Huang; Jia-Sheng Wang; Lili Tang (Environmental Pollution, 2024)

Receiver function image of the mantle transition zone beneath western China: Fragmented subduction and counterflow upwelling - Zheng Tang; Jordi Julià; Walter D. Mooney; Yanqiang Wu (Earth and Planetary Science Letters, 2024)

Training with reduced carbohydrate availability affects markers of bone resorption and formation in male academy soccer players from the English Premier League - Reuben Stables; Liam Anderson; Craig Sale; Marcus P. Hannon; Rachel Dunn; Jonathan C. Y. Tang; William D. Fraser; Nessan B. Costello; Graeme L. Close; James P. Morton (European Journal of Applied Physiology, 2024)
Purpose To test the hypothesis that training with reduced carbohydrate (CHO) availability increases bone resorption in adolescent soccer players. Methods In a randomised crossover design, ten male players (age: 17.4 ± 0.8 years) from an English Premier League academy completed an acute 90-min field-based training session (occurring between 10:30–12:00) in conditions of high (TRAIN HIGH; 1.5 g.kg −1 , 60 g, 1.5 g.kg −1 and 1.5 g.kg −1 consumed at 08:00, during training, 12:30 and 13:30, respectively) or low CHO availability (TRAIN LOW; 0 g.kg −1 ). Participants also completed a non-exercise trial (REST) under identical dietary conditions to TRAIN LOW. Venous blood samples were obtained at 08:30, 10:30, 12:30 and 14:30 for assessment of bone resorption (βCTX), bone formation (PINP) and calcium metabolism (PTH and ACa). Results External training load did not differ (all P > 0.05) between TRAIN HIGH and TRAIN LOW, as evident for total distance (5.6 ± 0.8; 5.5 ± 0.1 km), average speed (81 ± 9; 85 ± 12 m.min −1 ) and high-speed running (350 ± 239; 270 ± 89 m). Area under the curve for both βCTX and PINP was significantly greater ( P < 0.01 and P = 0.03) in TRAIN LOW versus TRAIN HIGH, whilst no differences in PTH or ACa ( P = 0.11 and P = 0.89) were observed between all three trials. Conclusion CHO restriction before, during and after an acute soccer training session increased bone (re)modelling markers in academy players. Despite acute anabolic effects of bone formation, the long-term consequence of bone resorption may impair skeletal development and increase injury risk during growth and maturation.

A Comparison Between the Gaseous and Particulate Emissions from Diesel and Natural Gas Yard Tractors - Tianbo Tang; Hanwei Zhu; Tianyi Ma; Peng Hao; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Emission Control Science and Technology, 2024)

Simultaneous electrochemical removal of three microcystin congeners and sulfamethoxazole in natural water - Xiaonan Tang; Alan D. Steinman; Yan Xu; Qingju Xue; Liqiang Xie (Chemosphere, 2024)

Eutrophication impacts the distribution and functional traits of viral communities in lakes - Qiue Zhang; Yanxuan Xiong; Jinhong Zhang; Boya Liu; Tianyi Chen; Shufeng Liu; Chenyuan Dang; Wei D. Xu; Hafiz Adeel Ahmad; Tang Liu (Science of The Total Environment, 2024)

Discovery of a novel marine bacterial AIEgen that lights up specific G-quadruplexes - Wenkang Ye; Xinnan Wang; Parvej Alam; Changdong Liu; Monica C. Suen; Jianwei Tang; Herman H.Y. Sung; Ian D. Williams; Eric Y. Yu; Jacky W.Y. Lam; Guang Zhu; Ben-Zhong Tang; et al. (Chemical Engineering Journal, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

The impact of social media interventions on eating behaviours and diet in young people: a mixed-methods systematic review - Hao Tang; Esther M.F. van Sluijs; Marie Spreckley; Amy L. Ahern; Andrea D. Smith (Appetite, 2024)

Understanding microwave heating of oils - Xu Zhou; Piotr Czekala; Marzena Olszewska–Placha; Bartlomiej Salski; Shuang Zhang; Patrick D. Pedrow; Shyam S. Sablani; Juming Tang (Journal of Food Engineering, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Chitosan-based electroconductive inks without chemical reaction for cost-effective and versatile 3D printing for electromagnetic interference (EMI) shielding and strain-sensing applications - Naresh D. Sanandiya; Avinash R. Pai; Shayan Seyedin; Fengzai Tang; Sabu Thomas; Fengwei Xie (Carbohydrate Polymers, 2024)

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

Effects of Bulleyaconitine A on Extracellular Matrix Secretion and Expression of Related Proteins in Acetaldehyde-Activated Hepatic Stellate Cells - Q. W. Song; Y. P. Yuan; Q. S. Sun; X. D. Zhan; Y. X. Jiang; X. N. Tang (Bulletin of Experimental Biology and Medicine, 2024)

Novel Multiplexed High Throughput Screening of Selective Inhibitors for Drug-Metabolizing Enzymes Using Human Hepatocytes - Jianhua Liu; Daria Vernikovskaya; Gary Bora; Anthony Carlo; Woodrow Burchett; Samantha Jordan; Lloyd Wei Tat Tang; Joy Yang; Ye Che; George Chang; Matthew D. Troutman; Li Di (The AAPS Journal, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

Decomposition of bark beetle-attacked trees after mortality varies across forests - N.A. Clay; J.D. Tang; C.M. Siegert; J.T. Thomason; N. Benedetto; D. Day; K. Pace; O. Leverón; R.W. Hofstetter; J.J. Riggins (Forest Ecology and Management, 2024)

In-use NOx and black carbon emissions from heavy-duty freight diesel vehicles and near-zero emissions natural gas vehicles in California's San Joaquin Air Basin - Tianyi Ma; Chengguo Li; Ji Luo; Chas Frederickson; Tianbo Tang; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Science of The Total Environment, 2024)

A numerical study of complex fractures propagation path in naturally fractured gas shale: Reorientation, deflection and convergence - Xuanhe Tang; Haiyan Zhu; Peng Zhao; Bo Zeng; Meng Zhao; Maurice B. Dusseault; John D. McLennan (Gas Science and Engineering, 2024)

In vitro fermentation characteristics of blueberry anthocyanins and their impacts on gut microbiota from obese human - Lujing Xu; Zhaocheng Tang; Daniela D. Herrera-Balandrano; Zeyu Qiu; Bin Li; Yiyun Yang; Wuyang Huang (Food Research International, 2024)

Effects of wavelength on the treatment of contaminants of emerging concern by UV-assisted homogeneous advanced oxidation/reduction processes - Liang Tang; Aozhou Li; Minghao Kong; Dionysios D. Dionysiou; Xiaodi Duan (Science of The Total Environment, 2023)

Microwave heating based on solid-state generators: New insights into heating pattern, uniformity, and energy absorption in foods - Xu Zhou; Zhongwei Tang; Patrick D. Pedrow; Shyam S. Sablani; Juming Tang (Journal of Food Engineering, 2023)

The stage-specific toxicity of per- and polyfluoroalkyl substances (PFAS) in nematode Caenorhabditis elegans - Seth D. Currie; Joseph Patrick Doherty; Kathy S. Xue; Jia-Sheng Wang; Lili Tang (Environmental Pollution, 2023)

Unexpected moderate contribution of intermediate volatility organic compounds from gasoline vehicle emission to secondary organic aerosol formation in summer of Beijing - Rongzhi Tang; Song Guo; Quanyang Lu; Kai Song; Yuanzheng Gong; Rui Tan; Kefan Liu; Hui Wang; Ying Yu; Ruizhe Shen; Shiyi Chen; Limin Zeng; et al. (Atmospheric Research, 2023)

The severity of foreign direct investment components on China's carbon productivity - Xin Sheng; Rui Yi; Decai Tang; David D. Lansana; Bright Obuobi (Journal of Cleaner Production, 2023)

Expanding the ethanol blend wall in California: Emissions comparison between E10 and E15 - Tianbo Tang; Cavan McCaffery; Tianyi Ma; Peng Hao; Thomas D. Durbin; Kent C. Johnson; Georgios Karavalakis (Fuel, 2023)

Catalytic activity and anti-passivation of single iron atoms and atomic clusters co-stabilized on carbonized waste polystyrene plastic - Shengjia Ma; Shuai Tang; Tao Zhang; Wei Jin; Hui Zhu; Yaping Zhao; Dionysios D. Dionysiou (Chemical Engineering Journal, 2023)

Optimization modeling and mechanism discussion on specific industrial coal-washing wastewater treatment - Y. Pan; D. Wang; K. Mei; T. Tang (International Journal of Environmental Science and Technology, 2023)

The influence of industrial structure transformation on urban resilience based on 110 prefecture-level cities in the Yangtze River - Decai Tang; Jiannan Li; Ziqian Zhao; Valentina Boamah; David D. Lansana (Sustainable Cities and Society, 2023)

Multi-elements characteristic and potential risk of heavy metals in MOUTAN CORTEX from Anhui Province, China - X. Xue; G. Liu; Q. Tang; H. Shi; D. Wu; C. Jin; H. Zhao; Y. Wei; Y. Zhang (International Journal of Environmental Science and Technology, 2023)

Moving forward with COVID-19: Future research prospects of wastewater-based epidemiology methodologies and applications - Guangming Jiang; Yanchen Liu; Song Tang; Masaaki Kitajima; Eiji Haramoto; Sudipti Arora; Phil M. Choi; Greg Jackson; Patrick M. D'Aoust; Robert Delatolla; Shuxin Zhang; Ying Guo; et al. (Current Opinion in Environmental Science & Health, 2023)

Identification and genome sequencing of an influenza H3N2 variant in wastewater from elementary schools during a surge of influenza A cases in Las Vegas, Nevada - Van Vo; Anthony Harrington; Ching-Lan Chang; Hayley Baker; Michael A. Moshi; Nabih Ghani; Jose Yani Itorralba; Richard L. Tillett; Elizabeth Dahlmann; Natnael Basazinew; Richard Gu; Tiffany D. Familara; et al. (Science of The Total Environment, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Sedimentary geochemistry mediated by a specific hydrological regime in the water level fluctuation zone of the Three Gorges Reservoir, China - Dil Khurram; Yuhai Bao; Qiang Tang; Xiubin He; Jinlin Li; Jean de D. Nambajimana; Gratien Nsabimana (Environmental Science and Pollution Research, 2023)

Heating performance of microwave ovens powered by magnetron and solid-state generators - Xu Zhou; Patrick D. Pedrow; Zhongwei Tang; Stewart Bohnet; Shyam S. Sablani; Juming Tang (Innovative Food Science & Emerging Technologies, 2023)

Three-Dimensional Ultrasound Localization Microscopy with Bipartite Graph-Based Microbubble Pairing and Kalman-Filtering-Based Tracking on a 256-Channel Verasonics Ultrasound System with a 32 × 32 Matrix Array - U-Wai Lok; Chengwu Huang; Joshua D. Trzasko; Yohan Kim; Fabrice Lucien; Shanshan Tang; Ping Gong; Pengfei Song; Shigao Chen (Journal of Medical and Biological Engineering, 2022)
Purpose Three-dimensional (3D) ultrasound localization microscopy (ULM) using a 2-D matrix probe and microbubbles (MBs) has recently been proposed to visualize microvasculature in three spatial dimensions beyond the ultrasound diffraction limit. However, 3D ULM has several limitations, including: (1) high system complexity, (2) complex MB flow dynamics in 3D, and (3) extremely long acquisition time that had to be addressed. Method To reduce the system complexity while maintaining high image quality, we used a sub-aperture process to reduce received channel counts. To address the second issue, a 3D bipartite graph-based method with Kalman filtering-based tracking was used in this study for MB tracking. An MB separation approach was incorporated to separate high concentration MB data into multiple, sparser MB datasets, allowing better MB localization and tracking for a limited acquisition time. Results The proposed method was first validated in a flow channel phantom, showing improved spatial resolutions compared with the contrasted enhanced power Doppler image. Then the proposed method was evaluated with an in vivo chicken embryo brain dataset. Results showed that the reconstructed 3D super-resolution image achieved a spatial resolution of around 52 μm (smaller than the wavelength of around 200 μm). Conclusion A lower system complexity of 3D ULM has been proposed. In addition, our proposed 3D ULM provided the capability of 3D motion compensation and MB tracking. Microvessels that cannot be resolved clearly using localization only, can be well identified with the proposed method.

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Polymetallic (zinc and cadmium) hyperaccumulation in the Australian legume Crotalaria novae-hollandiae compared to Crotalaria cunninghamii - Roger H. Tang; Philip N. Nkrumah; Peter D. Erskine; Antony van der Ent (Plant and Soil, 2022)
Purpose Hyperaccumulators are plants with the ability to tolerate and accumulate high concentrations of potentially phytotoxic metals. The Australian legume Crotalaria novae-hollandiae accumulates remarkably high concentrations of zinc (Zn), cadmium (Cd) and copper (Cu) in its shoots when growing on metalliferous (Zn-Cd ‘calamine’) soils. This study aimed to investigate zinc-cadmium tolerance in C. novae-hollandiae and to compare it with the closely related, but non-metalliferous, C. cunninghamii . Methods Crotalaria cunninghamii and C. novae-hollandiae were exposed to Zn (3–1000 μM) and Cd (0–60 μM) treatments in hydroponics culture. At the end of the experiment, harvested plants were segmented into roots, old and young stems, old and young leaves for elemental analysis with Inductively coupled plasma atomic emission spectroscopy (ICP-AES). Laboratory-based micro-X-ray fluorescence (μXRF) analysis was used to elucidate elemental distribution in a shoot and in leaflets. Results Crotalaria cunninghamii accumulated up to 1210 μg Zn g −1 and 47.6 μg Cd g −1 in its leaves, with a 75% reduction in biomass in the Zn treatment. Crotalaria novae-hollandiae accumulated up to 16,600 μg Zn g −1 and 1250 μg Cd g −1 , with a 70% increase in biomass when exposed to Zn. The species both exhibited chlorosis and stunted growth in the Cd treatments, while only C. cunninghamii exhibited toxicity symptoms in Zn treatment. Conclusions Crotalaria novae-hollandiae has limited tolerance for Cd and based on the accumulation and distribution of foliar Zn and Cd it is suspected that C. novae-hollandiae has different uptake and tolerance mechanisms when compared to other widely studied Zn-Cd hyperaccumulators (such as Noccaea caerulescens and Arabidopsis halleri ).

Mechanical Properties and Energy Damage Evolution Characteristics of Coal Under Cyclic Loading and Unloading - Z. W. Ding; J. D. Jia; Q. B. Tang; X. F. Li (Rock Mechanics and Rock Engineering, 2022)

GIS-based landslide susceptibility mapping using ensemble methods for Fengjie County in the Three Gorges Reservoir Region, China - W. Gong; M. Hu; Y. Zhang; H. Tang; D. Liu; Q. Song (International Journal of Environmental Science and Technology, 2022)

Impoundment increases methane emissions in Phragmites ‐invaded coastal wetlands - Rebecca Sanders‐DeMott; Meagan J. Eagle; Kevin D. Kroeger; Faming Wang; Thomas W. Brooks; Jennifer A. O'Keefe Suttles; Sydney K. Nick; Adrian G. Mann; Jianwu Tang (Global Change Biology, 2022)
Saline tidal wetlands are important sites of carbon sequestration and produce negligible methane (CH 4 ) emissions due to regular inundation with sulfate‐rich seawater. Yet, widespread management of coastal hydrology has restricted tidal exchange in vast areas of coastal wetlands. These ecosystems often undergo impoundment and freshening, which in turn cause vegetation shifts like invasion by Phragmites , that affect ecosystem carbon balance. Understanding controls and scaling of carbon exchange in these understudied ecosystems is critical for informing climate consequences of blue carbon restoration and/or management interventions. Here, we (1) examine how carbon fluxes vary across a salinity gradient (4–25 psu) in impounded and natural, tidally unrestricted Phragmites wetlands using static chambers and (2) probe drivers of carbon fluxes within an impounded coastal wetland using eddy covariance at the Herring River in Wellfleet, MA, United States. Freshening across the salinity gradient led to a 50‐fold increase in CH 4 emissions, but effects on carbon dioxide (CO 2 ) were less pronounced with uptake generally enhanced in the fresher, impounded sites. The impounded wetland experienced little variation in water‐table depth or salinity during the growing season and was a strong CO 2 sink of −352 g CO 2 ‐C m −2 year −1 offset by CH 4 emission of 11.4 g CH 4 ‐C m −2 year −1 . Growing season CH 4 flux was driven primarily by temperature. Methane flux exhibited a diurnal cycle with a night‐time minimum that was not reflected in opaque chamber measurements. Therefore, we suggest accounting for the diurnal cycle of CH 4 in Phragmites , for example by applying a scaling factor developed here of ~0.6 to mid‐day chamber measurements. Taken together, these results suggest that although freshened, impounded wetlands can be strong carbon sinks, enhanced CH 4 emission with freshening reduces net radiative balance. Restoration of tidal flow to impounded ecosystems could limit CH 4 production and enhance their climate regulating benefits.

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Impact of cyclic wetting and drying on slate properties in the Miaowei Reservoir area, southwest China - Peiwu Shen; Huiming Tang; Dwayne D. Tannant; Yibing Ning (Bulletin of Engineering Geology and the Environment, 2022)

Fully-automated SPE coupled to UHPLC-MS/MS method for multiresidue analysis of 26 trace antibiotics in environmental waters: SPE optimization and method validation - Ming Zheng; Suwen Tang; Yangyang Bao; Kevin D. Daniels; Zuo Tong How; Mohamed Gamal El-Din; Jie Wang; Liang Tang (Environmental Science and Pollution Research, 2022)

Soil-plant relationships of metallophytes of the zinc-lead-copper Dugald River gossan, Queensland, Australia - Roger H. Tang; Peter D. Erskine; Philip Nti Nkrumah; Guillaume Echevarria; Antony van der Ent (Plant and Soil, 2022)

Modeling of the Correlation Between Mineral Size and Shale Pore Structure at Meso- and Macroscales - W. D. Zhou; S. Y. Xie; Z. Y. Bao; E. J. M. Carranza; Y. Wang; M. L. Tang (Mathematical Geosciences, 2022)

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Genotype/Phenotype Interactions and First Steps Toward Targeted Therapy for Sphingosine Phosphate Lyase Insufficiency Syndrome - Julie D. Saba; Nancy Keller; Jen-Yeu Wang; Felicia Tang; Avi Slavin; Yizhuo Shen (Cell Biochemistry and Biophysics, 2021)

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Spatiotemporal impact of major events on air quality based on spatial differences-in-differences model: big data analysis from China - Ji Guo; Xianhua Wu; Yingying Guo; Yinshan Tang; Michael D. Dzandu (Natural Hazards, 2021)

Remodeling of Arctic char ( Salvelinus alpinus ) lipidome under a stimulated scenario of Arctic warming - Chao Wang; Yufeng Gong; Fuchang Deng; Enmin Ding; Jie Tang; Garry Codling; Jonathan K. Challis; Derek Green; Jing Wang; Qiliang Chen; Yuwei Xie; Shu Su; et al. (Global Change Biology, 2021)
Arctic warming associated with global climate change poses a significant threat to populations of wildlife in the Arctic. Since lipids play a vital role in adaptation of organisms to variations in temperature, high‐resolution mass‐spectrometry‐based lipidomics can provide insights into adaptive responses of organisms to a warmer environment in the Arctic and help to illustrate potential novel roles of lipids in the process of thermal adaption. In this study, we studied an ecologically and economically important species—Arctic char ( Salvelinus alpinus )—with a detailed multi‐tissue analysis of the lipidome in response to chronic shifts in temperature using a validated lipidomics workflow. In addition, dynamic alterations in the hepatic lipidome during the time course of shifts in temperature were also characterized. Our results showed that early life stages of Arctic char were more susceptible to variations in temperature. One‐year‐old Arctic char responded to chronic increases in temperature with coordinated regulation of lipids, including headgroup‐specific remodeling of acyl chains in glycerophospholipids (GP) and extensive alterations in composition of lipids in membranes, such as less lyso‐GPs, and more ether‐GPs and sphingomyelin. Glycerolipids (e.g., triacylglycerol, TG) also participated in adaptive responses of the lipidome of Arctic char. Eight‐week‐old Arctic char exhibited rapid adaptive alterations of the hepatic lipidome to stepwise decreases in temperature while showing blunted responses to gradual increases in temperature, implying an inability to adapt rapidly to warmer environments. Three common phosphatidylethanolamines (PEs) (PE 36:6|PE 16:1_20:5, PE 38:7|PE 16:1_22:6, and PE 40:7|PE 18:1_22:6) were finally identified as candidate lipid biomarkers for temperature shifts via machine learning approach. Overall, this work provides additional information to a better understanding of underlying regulatory mechanisms of the lipidome of Arctic organisms in the face of near‐future warming.

Tackling G × E × M interactions to close on-farm yield-gaps: creating novel pathways for crop improvement by predicting contributions of genetics and management to crop productivity - Mark Cooper; Kai P. Voss-Fels; Carlos D. Messina; Tom Tang; Graeme L. Hammer (Theoretical and Applied Genetics, 2021)
Key message Climate change and Genotype-by-Environment-by-Management interactions together challenge our strategies for crop improvement. Research to advance prediction methods for breeding and agronomy is opening new opportunities to tackle these challenges and overcome on-farm crop productivity yield-gaps through design of responsive crop improvement strategies. Abstract Genotype-by-Environment-by-Management (G × E × M) interactions underpin many aspects of crop productivity. An important question for crop improvement is “How can breeders and agronomists effectively explore the diverse opportunities within the high dimensionality of the complex G × E × M factorial to achieve sustainable improvements in crop productivity?” Whenever G × E × M interactions make important contributions to attainment of crop productivity, we should consider how to design crop improvement strategies that can explore the potential space of G × E × M possibilities, reveal the interesting Genotype–Management (G–M) technology opportunities for the Target Population of Environments (TPE), and enable the practical exploitation of the associated improved levels of crop productivity under on-farm conditions. Climate change adds additional layers of complexity and uncertainty to this challenge, by introducing directional changes in the environmental dimension of the G × E × M factorial. These directional changes have the potential to create further conditional changes in the contributions of the genetic and management dimensions to future crop productivity. Therefore, in the presence of G × E × M interactions and climate change, the challenge for both breeders and agronomists is to co-design new G–M technologies for a non-stationary TPE. Understanding these conditional changes in crop productivity through the relevant sciences for each dimension, Genotype, Environment, and Management, creates opportunities to predict novel G–M technology combinations suitable to achieve sustainable crop productivity and global food security targets for the likely climate change scenarios. Here we consider critical foundations required for any prediction framework that aims to move us from the current unprepared state of describing G × E × M outcomes to a future responsive state equipped to predict the crop productivity consequences of G–M technology combinations for the range of environmental conditions expected for a complex, non-stationary TPE under the influences of climate change.

Global transcriptomic profiles of circulating leucocytes in early lactation cows with clinical or subclinical mastitis - Zhangrui Cheng; Laura Buggiotti; Mazdak Salavati; Cinzia Marchitelli; Sergio Palma-Vera; Alistair Wylie; Haruko Takeda; Lijing Tang; Mark A. Crowe; D. Claire Wathes; Mark Crowe; Niamh McLoughlin; et al. (Molecular Biology Reports, 2021)

Recent advances on the role of cytotoxic T lymphocytes in the pathogenesis of spondyloarthritis - Michael Tang; Robert D. Inman (Seminars in Immunopathology, 2021)

Prevalence of Depression or Depressive Symptoms in Patients with Narcolepsy: a Systematic Review and Meta-Analysis - Xiao Li; Larry D. Sanford; Qiang Zong; Ye Zhang; Lu Tan; Taomei Li; Rong Ren; Junying Zhou; Fang Han; Xiangdong Tang (Neuropsychology Review, 2021)

Development and spatial application of a submerged aquatic vegetation model for Cootes Paradise Marsh, Ontario, Canada - Rex W. K. Tang; Susan E. Doka; Jonathan D. Midwood; Jesse M. Gardner Costa (Aquatic Sciences, 2021)

Genetic determinism of prickles in rose - N. N. Zhou; K. X. Tang; J. Jeauffre; T. Thouroude; D. C. Lopez Arias; F. Foucher; L. Hibrand-Saint Oyant (Theoretical and Applied Genetics, 2020)

Mild acidity likely accelerates the physiological matriptase autoactivation process: a comparative study between spontaneous and acid-induced matriptase zymogen activation - Bailing Jia; Hamishi A. Thompson; Robert B. Barndt; Yi-Lin Chiu; Mon-Juan Lee; See-Chi Lee; Jehng-Kang Wang; Hung-Jen Tang; Chen-Yong Lin; Michael D. Johnson (Human Cell, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Stable isotopes reveal effects of natural drivers and anthropogenic pressures on isotopic niches of invertebrate communities in a large subtropical river of China - Sai Wang; Lin-Hui Su; Bang-Ke Luo; Ying-Jun Qin; Simon D. Stewart; Jin-Peng Tang; Tuan-Tuan Wang; Yang Yang; Gong Cheng (Environmental Science and Pollution Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

A statistical method to construct wind speed at turbine height for study of wind power in China - X. Zhou; J. Qin; H. D. Li; W. Tang; X. Pan; B. Huang; X. Li (Theoretical and Applied Climatology, 2020)

Determining Haemodynamic Wall Shear Stress in the Rabbit Aorta In Vivo Using Contrast-Enhanced Ultrasound Image Velocimetry - K. Riemer; E. M. Rowland; C. H. Leow; M. X. Tang; P. D. Weinberg (Annals of Biomedical Engineering, 2020)
Abnormal blood flow and wall shear stress (WSS) can cause and be caused by cardiovascular disease. To date, however, no standard method has been established for mapping WSS in vivo . Here we demonstrate wide-field assessment of WSS in the rabbit abdominal aorta using contrast-enhanced ultrasound image velocimetry (UIV). Flow and WSS measurements were made independent of beam angle, curvature or branching. Measurements were validated in an in silico model of the rabbit thoracic aorta with moving walls and pulsatile flow. Mean errors over a cardiac cycle for velocity and WSS were 0.34 and 1.69%, respectively. In vivo time average WSS in a straight segment of the suprarenal aorta correlated highly with simulations (PC = 0.99) with a mean deviation of 0.29 Pa or 5.16%. To assess fundamental plausibility of the measurement, UIV WSS was compared to an analytic approximation derived from the Poiseuille equation; the discrepancy was 17%. Mapping of WSS was also demonstrated in regions of arterial branching. High time average WSS (TAWSS xz = 3.4 Pa) and oscillatory flow (OSI xz = 0.3) were observed near the origin of conduit arteries. In conclusion, we have demonstrated that contrast-enhanced UIV is capable of measuring spatiotemporal variation in flow velocity, arterial wall location and hence WSS in vivo with high accuracy over a large field of view.

FGF-2 Attenuates Neuronal Apoptosis via FGFR3/PI3k/Akt Signaling Pathway After Subarachnoid Hemorrhage - Takeshi Okada; Budbazar Enkhjargal; Zachary D. Travis; Umut Ocak; Jiping Tang; Hidenori Suzuki; John H. Zhang (Molecular Neurobiology, 2019)

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Influences of immunostimulants on phagocytes in cultured fish: a mini review - Emmanuel D. Abarike; Felix K.A. Kuebutornye; Jichang Jian; Jufen Tang; Yishan Lu; Jia Cai (Reviews in Aquaculture, 2019)
Lower vertebrates like fish mostly depend on innate immunity as the first line of defence against invading pathogens. One of the defence mechanisms in innate immunity for fish is the use of phagocytic cells such as monocytes, macrophages, neutrophils, mast cells and dendritic cells in fighting pathogens. These cellular cells employ a variety of mechanisms in protecting fish including but not limited to; the use of pattern recognition receptors and antigen presenting cells to detect the presence of pathogens in host, neutralising them using measures including; inflammation, production of lysosomal enzymes released into the phagosome to neutralising pathogens and prevention of systemic autoimmunity by apoptosis. Some phagocytic cells play the extra role of serving as a bridge between innate and adaptive immunity in fish. Recent accumulating data showed that phagocyte cell activity in fish could be enhanced by a natural or chemical substance (immunostimulants) that stimulates the immune system in fish principally meant to enhance the immune response mechanisms. In this review, the main focus is on elucidating the distinct phagocytic mechanisms played by monocytes, macrophages, neutrophils, mast cells and dendritic cells as principal phagocytes in immune defence and how their activities are influenced by immunostimulants in cultured fish.

Identification and Expression Profiling of Odorant Receptor Protein Genes in Sitophilus zeamais (Coleoptera: Curculionoidea) Using RT-qPCR - Q Tang; Y Zhang; C Shen; D Xia (Neotropical Entomology, 2019)

Model-Based and Model-Free Techniques for Amyotrophic Lateral Sclerosis Diagnostic Prediction and Patient Clustering - Ming Tang; Chao Gao; Stephen A. Goutman; Alexandr Kalinin; Bhramar Mukherjee; Yuanfang Guan; Ivo D. Dinov (Neuroinformatics, 2019)

Indole-3-acetylaspartate and indole-3-acetylglutamate, the IAA-amide conjugates in the diploid strawberry achene, are hydrolyzed in growing seedlings - Qian Tang; Peng Yu; Molly Tillmann; Jerry D. Cohen; Janet P. Slovin (Planta, 2019)

Improving engraftment of hepatocyte transplantation using alpha-1 antitrypsin as an immune modulator - Charlotte Lee; Anil Dhawan; Valeria Iansante; Celine Filippi; Ragai Mitry; Joanne Tang; Simon Walker; Raquel Fernandez DaCosta; Siddharth Sinha; Robin D. Hughes; Maria Koulmanda; Emer Fitzpatrick (Journal of Molecular Medicine, 2019)

Residue decomposition and soil carbon priming in three contrasting soils previously exposed to elevated CO2 - Clayton R. Butterly; Roger D. Armstrong; Deli Chen; Caixian Tang (Biology and Fertility of Soils, 2019)

Indirect effects of bark beetle-generated dead wood on biogeochemical and decomposition processes in a pine forest - Courtney M. Siegert; Natalie A. Clay; Juliet D. Tang; Lisa G. Garrigues; John J. Riggins (Oecologia, 2018)

A hybrid proline-rich cell-wall protein gene JsPRP1 from Juglans sigillata Dode confers both biotic and abiotic stresses in transgenic tobacco plants - D. Q. Liu; Q. Han; T. Shah; C. Y. Chen; Q. Wang; B. F. Tang; F. Ge (Trees, 2018)

Camelina sativa, an oilseed at the nexus between model system and commercial crop - Meghna R. Malik; Jihong Tang; Nirmala Sharma; Claire Burkitt; Yuanyuan Ji; Marie Mykytyshyn; Karen Bohmert-Tatarev; Oliver Peoples; Kristi D. Snell (Plant Cell Reports, 2018)

Global patterns of Rhododendron diversity: The role of evolutionary time and diversification rates - Nawal Shrestha; Zhiheng Wang; Xiangyan Su; Xiaoting Xu; Lisha Lyu; Yunpeng Liu; Dimitar Dimitrov; Jonathan D. Kennedy; Qinggang Wang; Zhiyao Tang; Xiaojuan Feng (Global Ecology and Biogeography, 2018)
Aim Understanding the evolution of the latitudinal diversity gradient (i.e. increase in species diversity towards the tropics) is a prominent issue in ecology and biogeography. Disentangling the relative contributions of environment and evolutionary history in shaping this gradient remains a major challenge because their relative importance has been found to vary across regions and taxa. Here, using the global distributions and a molecular phylogeny of Rhododendron , one of the largest genera of flowering plants, we aim to compare the relative contributions of contemporary environment, evolutionary time and diversification rates in generating extant species diversity patterns. Location Global. Time period Undefined. Major taxa studied Rhododendron . Methods We compiled the global distributions of all Rhododendron species, and constructed a dated molecular phylogeny using nine chloroplast genes and seven nuclear regions. By integrating these two datasets, we estimated the temporal trends of Rhododendron diversification, and explored the global patterns of its species diversity, net diversification rates, and species ages. Next, we reconstructed the geographical ancestral area of the clade. Finally, we compared the relative contribution of contemporary environment, time‐for‐speciation, and diversification rates on the species diversity pattern of Rhododendron . Results In contrast to the predictions of the time‐for‐speciation hypothesis, we found that although Rhododendron originated at a temperate latitude, its contemporary species diversity is highest in the tropics/subtropics, suggesting an into‐the‐tropics colonization for this genus. We found that the elevated diversification induced by heterogeneous environmental conditions in the tropics/subtropics shapes the global pattern of Rhododendron diversity. Main conclusions Our findings support tropical and subtropical mountains as not only biodiversity and endemism hotspots, but also as cradles for the diversification of Rhododendron . Our study emphasizes the need of unifying ecological and evolutionary approaches in order to gain comprehensive understanding of the mechanisms underlying the global patterns of plant diversity.

Front Cover - Nawal Shrestha; Zhiheng Wang; Xiangyan Su; Xiaoting Xu; Lisha Lyu; Yunpeng Liu; Dimitar Dimitrov; Jonathan D. Kennedy; Qinggang Wang; Zhiyao Tang; Xiaojuan Feng (Global Ecology and Biogeography, 2018)

Variability in circulating gas emboli after a same scuba diving exposure - V. Papadopoulou; P. Germonpré; D. Cosgrove; R. J. Eckersley; P. A. Dayton; G. Obeid; A. Boutros; M.-X. Tang; S. Theunissen; C. Balestra (European Journal of Applied Physiology, 2018)

Evolutionary relationships of two balitorids (Cypriniformes, Balitoridae) revealed by comparative mitogenomics - Li‐Xia Shi; Chen Zhang; Yin‐Ping Wang; Qiong‐Ying Tang; Patrick D. Danley; Huan‐Zhang Liu (Zoologica Scripta, 2018)
Balitoridae, a family within the Cypriniformes, inhabit torrential mountain streams in Asia. Although they have long fascinated ichthyologists for their numerous adaptations to this tumultuous environment, the evolutionary history of this group remains poorly understood. In this study, we investigate the evolutionary relationships of the balitorids with particular attention to the phylogenetic placement of two balitorid species, Yaoshania pachychulis and Erromyzon kalotaenia . Both species have extremely limited distributions, they are limited to Mt. Dayaoshan of the Pearl River in China and require dedicated conservation plans. However, little is known about their evolutionary relationships to other balitorids. Here, we examined the evolutionary relationships of Y. pachychulis and E. kalotaenia to each other and other balitorids through sequencing the complete mitochondrial genomes of nine balitorid individuals. For the newly sequenced balitorids, the length of the whole mitogenome, gene arrangement and their base composition are similar to those of other bony fishes. Analyses based on these newly sequenced mitogenomes and an additional 50 previously published mitogenomes show that Y. pachychulis and E. kalotaenia cluster as different clade within the subfamily Gastromyzontinae. The genetic distance between these two species ranges from 0.127 ± 0.003 to 0.132 ± 0.004 which is slightly higher than that between some genera (e.g. the distance between Vanmanenia and Metahomaloptera is 0.127 ± 0.004). Therefore, it is reasonable to assign Y. pachychulis and E. kalotaenia to different genera. Phylogenetic signal assessment suggested that ND 1 , ND 4 and ND 5 genes as well as their concatenated subsets perform relatively well in reconstructing the Cobitoidea phylogeny. The divergence time estimation indicated that the balitorids distributed in Mt. Dayaoshan might have originated and evolved following the flattening and uplifting of the Yunnan–Guizhou Plateau during the late Miocene to late Pliocene.

Light scattering measurements in electron-beam sterilized corneas stored in recombinant human serum albumin - Khoa D. Tran; Yan Li; Jeffrey D. Holiman; Maolong Tang; David Huang; Michael D. Straiko; Christopher G. Stoeger (Cell and Tissue Banking, 2018)

Saurogobio punctatus sp. nov., a new cyprinid gudgeon (Teleostei: Cypriniformes) from the Yangtze River, based on both morphological and molecular data - Q. Y. Tang; X. B. Li; D. Yu; Y. R. Zhu; B. Q. Ding; H. Z. Liu; P. D. Danley (Journal of Fish Biology, 2018)
A new cyprinid gudgeon, Saurogobio punctatus sp. nov., is described based on specimens collected from the Yangtze River, China. The new species can be distinguished from its congeners by differences in both morphology and the cytochrome b ( cytb ) gene sequence. Numerous minute blackish spots are scattered on dorsal and caudal fins in S. punctatus sp. nov. v . absent in the other seven valid Saurogobio species. The new species can be further distinguished from its congeners by the following unique combination of characters: a dorsal fin with eight branched rays; absence of scales in chest area before pectoral origin; upper and lower lips thick, covered with papillae; and a papillose mental pad approximately triangular. Morphologically, the new species most resembles the Chinese lizard gudgeon Saurogobio dabryi , but the new species lays yellowish adhesive eggs v . white pelagic eggs in S. dabryi . A phylogenetic analysis of all Saurogobio species based on cytb gene sequences indicated that S. punctatus sp. nov was distinctly separated from its congeners, with mean sequence divergence ranging from 12·6 to 21·0%. Therefore, molecular data further supported the distinctiveness of the new species.

Curcumin Attenuates Colistin-Induced Neurotoxicity in N2a Cells via Anti-inflammatory Activity, Suppression of Oxidative Stress, and Apoptosis - Chongshan Dai; Giuseppe D. Ciccotosto; Roberto Cappai; Shusheng Tang; Daowen Li; Sanlei Xie; Xilong Xiao; Tony Velkov (Molecular Neurobiology, 2018)

Hemodynamic Effects of Lipid-Based Oxygen Microbubbles via Rapid Intravenous Injection in Rodents - Katherine J. Black; Andrew T. Lock; Lindsay M. Thomson; Alexis R. Cole; Xiaoqi Tang; Brian D. Polizzotti; John N. Kheir (Pharmaceutical Research, 2017)

Abnormalities in brain white matter in adolescents with 22q11.2 deletion syndrome and psychotic symptoms - Zora Kikinis; Kang Ik K. Cho; Ioana L. Coman; Petya D. Radoeva; Sylvain Bouix; Yingying Tang; Ryan Eckbo; Nikos Makris; Jun Soo Kwon; Marek Kubicki; Kevin M. Antshel; Wanda Fremont; et al. (Brain Imaging and Behavior, 2017)

Quality assessment of groundwater from the south-eastern Arabian Peninsula - H. W. Zhang; Y. Q. Sun; Y. Li; X. D. Zhou; X. Z. Tang; P. Yi; A. Murad; S. Hussein; D. Alshamsi; A. Aldahan; Z. B. Yu; X. G. Chen; et al. (Environmental Monitoring and Assessment, 2017)

Fifteen species in one: deciphering the Brachionus plicatilis species complex (Rotifera, Monogononta) through DNA taxonomy - Scott Mills; J. Arturo Alcántara-Rodríguez; Jorge Ciros-Pérez; Africa Gómez; Atsushi Hagiwara; Kayla Hinson Galindo; Christian D. Jersabek; Reza Malekzadeh-Viayeh; Francesca Leasi; Jae-Seong Lee; David B. Mark Welch; Spiros Papakostas; et al. (Hydrobiologia, 2017)

Gain-of-function EGLN1 prolyl hydroxylase (PHD2 D4E:C127S) in combination with EPAS1 (HIF-2α) polymorphism lowers hemoglobin concentration in Tibetan highlanders - Tsewang Tashi; N. Scott Reading; Tanna Wuren; Xu Zhang; Lorna G. Moore; Hao Hu; Feng Tang; Anna Shestakova; Felipe Lorenzo; Tatiana Burjanivova; Parvaiz Koul; Prasenjit Guchhait; et al. (Journal of Molecular Medicine, 2017)

Subsessila turbinata gen. et. sp. nov. (Beltraniaceae), a Beltrania-like fungus from Thailand - Chuan-Gen Lin; Dong-Qin Dai; Darbhe J. Bhat; Kevin D. Hyde; Li-Zhou Tang; Chaiwat To-anun (Mycological Progress, 2017)

Cross‐scale intercomparison of climate change impacts simulated by regional and global hydrological models in eleven large river basins - F. F. Hattermann; V. Krysanova; S. N. Gosling; R. Dankers; P. Daggupati; C. Donnelly; M. Flörke; S. Huang; Y. Motovilov; S. Buda; T. Yang; C. Müller; et al. (Climatic Change, 2017)

Elevated CO2 induced rhizosphere effects on the decomposition and N recovery from crop residues - Clayton R. Butterly; Xiaojuan Wang; Roger D. Armstrong; Deli Chen; Caixian Tang (Plant and Soil, 2016)

A multi-center, controlled, randomized, open-label clinical study of levofloxacin for preventing infection during the perioperative period of ultrasound-guided transrectal prostate biopsy - L.-D. Qiao; S. Chen; X.-F. Wang; W.-M. Yang; Y.-J. Niu; C.-Z. Kong; W. Tang; X.-F. Gao; B.-K. Shi; Y.-Q. Na; X.-D. Zhang; J.-Y. Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Etiology and clinical features of 229 cases of bloodstream infection among Chinese HIV/AIDS patients: a retrospective cross-sectional study - T. Qi; R. Zhang; Y. Shen; L. Liu; D. Lowrie; W. Song; J. Chen; Z. Wang; J. Shen; R. Cai; L. Guan; B. Luo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Understanding marine dissolved organic matter production: Compositional insights from axenic cultures of Thalassiosira pseudonana - Emily M. Saad; Amelia F. Longo; Luke R. Chambers; Rixiang Huang; Claudia Benitez‐Nelson; Sonya T. Dyhrman; Julia M. Diaz; Yuanzhi Tang; Ellery D. Ingall (Limnology and Oceanography, 2016)

Parasitism Performance of Tetrastichus brontispae Ferriere over the Coconut Hispine Beetle, Brontispa longissima (Gestro) - K Liu; B L Fu; J R Lin; Y G Fu; Z Q Peng; Q A Jin; L D Tang (Neotropical Entomology, 2016)

Pore-scale and continuum simulations of solute transport micromodel benchmark experiments - M. Oostrom; Y. Mehmani; P. Romero-Gomez; Y. Tang; H. Liu; H. Yoon; Q. Kang; V. Joekar-Niasar; M. T. Balhoff; T. Dewers; G. D. Tartakovsky; E. A. Leist; et al. (Computational Geosciences, 2016)

Repositioning “old” drugs for new causes: identifying new inhibitors of prostate cancer cell migration and invasion - Esha T. Shah; Akanksha Upadhyaya; Lisa K. Philp; Tiffany Tang; Dubravka Skalamera; Jennifer Gunter; Colleen C. Nelson; Elizabeth D. Williams; Brett G. Hollier (Clinical & Experimental Metastasis, 2016)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Succulent species differ substantially in their tolerance and phytoextraction potential when grown in the presence of Cd, Cr, Cu, Mn, Ni, Pb, and Zn - Chengjun Zhang; Peter W. G. Sale; Gary J Clark; Wuxing Liu; Augustine I. Doronila; Spas D. Kolev; Caixian Tang (Environmental Science and Pollution Research, 2015)

A Real-Time Analysis and Feedback System for Quality Control of Dam Foundation Grouting Engineering - D. H. Zhong; F. G. Yan; M. C. Li; C. X. Huang; K. Fan; J. F. Tang (Rock Mechanics and Rock Engineering, 2015)

A review of the plant virus, viroid, liberibacter and phytoplasma records for New Zealand - S. Veerakone; J. Z. Tang; L. I. Ward; L. W. Liefting; Z. Perez-Egusquiza; B. S. M. Lebas; C. Delmiglio; J. D. Fletcher; P. L. Guy (Australasian Plant Pathology, 2015)

Identification of a novel HIV-1 intra-circulating recombinant form 01_AE in China: a descendant of the previously identified CRF01_AE transmission clusters 1 and 6 - ChuanYi Ning; XingGuang Li; WeiMing Tang; Bo Zhou; WeiPing Cai; Joseph D. Tucker (Science China Life Sciences, 2015)

Overexpression of an Aeluropus littoralis Parl. potassium transporter gene, AlHAK1, in cotton enhances potassium uptake and salt tolerance - J. F. Liu; S. L. Zhang; H. L. Tang; L. Z. Wu; L. J. Dong; L. D. Liu; W. L. Che (Euphytica, 2015)

A spaceborne assessment of cyclone impacts on Barents Sea surface temperature and chlorophyll - E. Morozov; D. Kondrik; A. Fedorova; D. Pozdnyakov; D. L. Tang; L. Pettersson (International Journal of Remote Sensing, 2015)

Linking shelf delta to deep-marine deposition in reservoir dispersal of the upper Oligocene strata in the Baiyun Sag, the northern South China Sea - S. H. Xu; Y. M. Wang; G. Q. Xu; G. D. Zeng; W. Guo; C. L. Gong; C. E. Cai; W. Tang; H. T. Zhuo; H. Q. Wan (Australian Journal of Earth Sciences, 2015)

A split airlift bioreactor for continuous culture of Glycyrrhiza inflata cell suspensions - G. R. Wang; Q. Z. Chen; N. Tang; B. L. Li; D. L. Fan; K. X. Tang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Asymmetric sensitivity of first flowering date to warming and cooling in alpine plants - S. P. Wang; F. D. Meng; J. C. Duan; Y. F. Wang; X. Y. Cui; S. L. Piao; H. S. Niu; G. P. Xu; C. Y. Luo; Z. H. Zhang; X. X. Zhu; M. G. Shen; et al. (Ecology, 2014)
Understanding how flowering phenology responds to warming and cooling (i.e., symmetric or asymmetric response) is needed to predict the response of flowering phenology to future climate change that will happen with the occurrence of warm and cold years superimposed upon a long‐term trend. A three‐year reciprocal translocation experiment was performed along an elevation gradient from 3200 m to 3800 m in the Tibetan Plateau for six alpine plants. Transplanting to lower elevation (warming) advanced the first flowering date (FFD) and transplanting to higher elevation (cooling) had the opposite effect. The FFD of early spring flowering plants (ESF) was four times less sensitive to warming than to cooling (by −2.1 d/°C and 8.4 d/°C, respectively), while midsummer flowering plants (MSF) were about twice as sensitive to warming than to cooling (−8.0 d/°C and 4.9 d/°C, respectively). Compared with pooled warming and cooling data, warming alone significantly underpredicted 3.1 d/°C for ESF and overestimated 1.7 d/°C for MSF. These results suggest that future empirical and experimental studies should consider nonlinear temperature responses that can cause such warming–cooling asymmetries as well as differing life strategies (ESF vs. MSF) among plant species.

Block caving-induced strata movement and associated surface subsidence: a numerical study based on a demonstration model - L. C. Li; C. A. Tang; X. D. Zhao; M. Cai (Bulletin of Engineering Geology and the Environment, 2014)

Impact of esterified bacteriochlorophylls on the biogenesis of chlorosomes in Chloroflexus aurantiacus - Yaya Wang; Dana M. Freund; Nikki M. Magdaong; Volker S. Urban; Harry A. Frank; Adrian D. Hegeman; Joseph Kuo-Hsiang Tang (Photosynthesis Research, 2014)

Application of SRAP markers in the identification of Stylosanthes guianensis hybrids - C. Q. Huang; G. D. Liu; C. J. Bai; W. Q. Wang; J. Tang (Molecular Biology Reports, 2014)

Expanding the clinical and mutational spectrum of Kaufman oculocerebrofacial syndrome with biallelic UBE3B mutations - Lina Basel-Vanagaite; Rüstem Yilmaz; Sha Tang; Miriam S. Reuter; Nils Rahner; Dorothy K. Grange; Megan Mortenson; Patrick Koty; Heather Feenstra; Kelly D. Farwell Gonzalez; Heinrich Sticht; Nathalie Boddaert; et al. (Human Genetics, 2014)

Vitamin D supplementation does not improve human skeletal muscle contractile properties in insufficient young males - Daniel J. Owens; Daniel Webber; Samuel G. Impey; Jonathan Tang; Timothy F. Donovan; William D. Fraser; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2014)

The truth about Pea mild mosaic virus - Z. Perez-Egusquiza; J. Z. Tang; L. I. Ward; J. D. Fletcher (Australasian Plant Pathology, 2014)

Effects of Surfactants on the Photolysis of Chlorothalonil on Pepper (Capsicum annuum var. grossum Sendt) - H.-X. Xiong; Y.-Q. Tan; T.-Z. Shi; R.-M. Hua; X.-W. Wu; H.-Q. Cao; X.-D. Li; J. Tang (Bulletin of Environmental Contamination and Toxicology, 2014)

An integrated model to assess critical rainfall thresholds for run-out distances of debris flows - Th. W. J. van Asch; C. Tang; D. Alkema; J. Zhu; W. Zhou (Natural Hazards, 2014)

Gonococcal endocarditis: a case report and literature review - S. Nie; Y. Wu; L. Huang; D. Pincus; Y.-W. Tang; X. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Sensing Biophysical Alterations of Human Lung Epithelial Cells (A549) in the Context of Toxicity Effects of Diesel Exhaust Particles - Yangzhe Wu; Gerald D. McEwen; Mingjie Tang; Tian Yu; James T. Dimmick; Anhong Zhou; Timothy A. Gilbertson; Roger A. Coulombe; John R. Stevens (Cell Biochemistry and Biophysics, 2013)

Effects of Dietary Copper on Growth, Digestive, and Brush Border Enzyme Activities and Antioxidant Defense of Hepatopancreas and Intestine for Young Grass Carp (Ctenopharyngodon idella) - Q. Q. Tang; L. Feng; W. D. Jiang; Y. Liu; J. Jiang; S. H. Li; S. Y. Kuang; L. Tang; X. Q. Zhou (Biological Trace Element Research, 2013)

Experimental study on cascading landslide dam failures by upstream flows - Gordon G. D. Zhou; P. Cui; H. Y. Chen; X. H. Zhu; J. B. Tang; Q. C. Sun (Landslides, 2013)

Numerical Modeling of Pore Pressure Influence on Fracture Evolution in Brittle Heterogeneous Rocks - S. Y. Wang; S. W. Sloan; S. G. Fityus; D. V. Griffiths; C. A. Tang (Rock Mechanics and Rock Engineering, 2013)

Image of a subsurface current core in the southern South China Sea - Q. S. Tang; D. X. Wang; J. B. Li; P. Yan; J. Li (Ocean Science, 2013)
A legacy seismic transect acquired on 30 and 31 May 2009 in the southern South China Sea (SCS) was reprocessed to reveal the thermohaline structure of the water column. In the study region, a mesoscale subsurface lens with extraordinary features was detected at 113.5° E, 11.5° N. It is centred at 450 m depth, occupies both the subsurface and intermediate water from 250 to 600 m, and has an intersection diameter of around 60 km. The simulated results from Hybrid Coordinate Ocean Model reveal an eddy-induced subsurface current running southwestward along the deep basin edge and suggest that the imaged lens is a snapshot of the subsurface current core rather than a subsurface eddy.

The effect of gait approach velocity on the broken escalator phenomenon - K.-S. Tang; D. Kaski; J. H. J. Allum; A. M. Bronstein (Experimental Brain Research, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

Grass Invasions Across a Regional Gradient are Associated with Declines in Belowground Carbon Pools - Timothy D. Kramer; Robert J. Warren; Yaya Tang; Mark A. Bradford (Ecosystems, 2012)

Plant invasion impacts on arthropod abundance, diversity and feeding consistent across environmental and geographic gradients - Yaya Tang; Robert J. Warren; Timothy D. Kramer; Mark A. Bradford (Biological Invasions, 2012)

Polymorphism of insulin-like growth factor 1 gene and its association with litter size in Small Tail Han sheep - J. N. He; B. Y. Zhang; M. X. Chu; P. Q. Wang; T. Feng; G. L. Cao; R. Di; L. Fang; D. W. Huang; Q. Q. Tang; N. Li (Molecular Biology Reports, 2012)

A novel HSI2 mutation in Arabidopsis affects the PHD-like domain and leads to derepression of seed-specific gene expression - Vijaykumar Veerappan; Jing Wang; Miyoung Kang; Joohyun Lee; Yuhong Tang; Ajay K. Jha; Huazhong Shi; Ravishankar Palanivelu; Randy D. Allen (Planta, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

Mitochondrial capture and incomplete lineage sorting in the diversification of balitorine loaches (Cypriniformes, Balitoridae) revealed by mitochondrial and nuclear genes - Qiong‐Ying Tang; Si‐Qing Liu; Dan Yu; Huan‐Zhang Liu; Patrick D. Danley (Zoologica Scripta, 2012)
Tang, Q.‐Y., Liu, S.‐Q., Yu, D., Liu, H.‐Z. & Danley, P.D. (2012) Mitochondrial capture and incomplete lineage sorting in the diversification of balitorine loaches (Cypriniformes, Balitoridae) revealed by mitochondrial and nuclear genes. — Zoologica Scripta , 41 , 233–247. Understanding the diversification of species is a central goal of evolutionary biological studies. One powerful tool to investigate the speciation process is molecular systematics. Here, we use molecular methods to investigate the evolution of balitorine loaches belonging to two genera, Lepturichthys and Jinshaia. Both genera contain only two species ( Lepturichthys fimbriata, Lepturichthys dolichopterus and Jinshaia sinensis and Jinshaia abbreviata ), all of which are endemic to China. These species share many morphological and ecological characters and exhibit overlapping distributions in the Upper Yangtze River. In this study, we used two mitochondrial genes (Cyt b and COI) and one nuclear gene (RAG1) to investigate the phylogenetic relationships within and between these two genera. Phylogenetic analyses and network construction based on mitochondrial and nuclear genes consistently supported the monophyly of Jinshaia . In contrast, the mitochondrial and nuclear genes yielded conflicting results in Lepturichthys . The phylogenetic analyses of mitochondrial sequences identify two distinct Lepturichthys lineages, Lepturichthys A and Lepturichthys B. Lepturichthys A includes most of L. fimbriata individuals from the Upper Yangtze River and is the sister group to all Jinshaia species. Lepturichthys B consists of the remaining L. fimbriata individuals from the Upper and Middle Yangtze River, and all L. dolichopterus individuals from the Minjiang River in Southeastern China. However, the analysis of the nuclear sequence indicates that the genus Lepturichthys is monophyletic and is only distantly related to Jinshaia . This incongruence suggests that introgressive hybridization might have occurred between L. fimbriata ( Lepturichthys A) and Jinshaia species. As a result of this hybridization event, L. fimbriata captured the mitochondrial genome of the sympatric Jinshaia species. This capture event appears to have occurred at least 1.74 million years ago. Additionally, L. fimbriata appears to be paraphyletic; the nuclear data indicated that L. dolichopterus forms a monophyletic clade nested within L. fimbriata . Because L. dolichopterus and L. fimbriata are allopatric and hybridization may not be possible, we suggest that the observed paraphyly of L. fimbriata is a product of incomplete lineage sorting. In addition, the reciprocal monophyly of J. sinensis and J. abbreviata could not be resolved. This may be the result of interspecific hybridization as these species occur sympatrically. However, incomplete lineage sorting may have caused the observed topology of the Jinshaia species. The data presented here illustrate the complex evolutionary history of the balitorine loach species: intergeneric hybridization and interspecific hybridization have likely occurred in this lineage. In addition, possible incomplete lineage sorting may further obscure the evolutionary history of this group. The complex relationships of the balitorine loaches provide a rich evolutionary system to study the creation of sympatric and sister species.

Polymorphism of 5′ regulatory region of ovine FSHR gene and its association with litter size in Small Tail Han sheep - M. X. Chu; X. H. Guo; C. J. Feng; Y. Li; D. W. Huang; T. Feng; G. L. Cao; L. Fang; R. Di; Q. Q. Tang; Y. H. Ma; K. Li (Molecular Biology Reports, 2012)

Formation and characteristics of post-earthquake debris flow: a case study from Wenjia gully in Mianzhu, Sichuan, SW China - H. Y. Ni; W. M. Zheng; Y. B. Tie; P. C. Su; Y. Q. Tang; R. G. Xu; D. W. Wang; X. Y. Chen (Natural Hazards, 2012)

Groundwater investigation on sand dunes area in southern part of Vietnam by magnetic resonance sounding - Nguyen V. Giang; Tang D. Nam; Maksim Bano (Acta Geophysica, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Typhoon-Ocean Interaction in the Western North Pacific: Part 1 - Eric D'Asaro; Peter Black; Luca Centurioni; Patrick Harr; Steven Jayne; I.I. Lin; Craig Lee; Jan Morzel; Rosalinda Mrvaljevic; Pearn Niiler; Luc Rainville; Thomas Stanford; et al. (Oceanography, 2011)

GDF9 as a candidate gene for prolificacy of Small Tail Han sheep - M. X. Chu; J. Yang; T. Feng; G. L. Cao; L. Fang; R. Di; D. W. Huang; Q. Q. Tang; Y. H. Ma; K. Li; N. Li (Molecular Biology Reports, 2011)

hnRNP F directs formation of an exon 4 minus variant of tumor-associated NADH oxidase (ENOX2) - Xiaoyu Tang; Vanessa D. Kane; Dorothy M. Morré; D. James Morré (Molecular and Cellular Biochemistry, 2011)

Sensitivity analysis of climatic parameters for sky classification - D. H. W. Li; H. L. Tang; K. L. Cheung; E. W. M. Lee; C. C. K. Cheng (Theoretical and Applied Climatology, 2011)

Mechanisms of chloride in cardiomyocyte anoxia-reoxygenation injury: the involvement of oxidative stress and NF-kappaB activation - D. Liu; H. He; G. L. Li; J. Chen; D. Yin; Z. P. Liao; L. Tang; Q. R. Huang; Z. F. Lai; M. He (Molecular and Cellular Biochemistry, 2011)

Occurrence of toxigenic fungi in ochratoxin A contaminated liquorice root - A.J. Chen; L.F. Huang; L.Z. Wang; D. Tang; F. Cai; W.W. Gao (Food Additives & Contaminants: Part A, 2011)

Serum estrogen levels and prostate cancer risk in the prostate cancer prevention trial: a nested case–control study - Song Yao; Cathee Till; Alan R. Kristal; Phyllis J. Goodman; Ann W. Hsing; Catherine M. Tangen; Elizabeth A. Platz; Frank Z. Stanczyk; Juergen K. V. Reichardt; Li Tang; Marian L. Neuhouser; Regina M. Santella; et al. (Cancer Causes & Control, 2011)

Long-term changes in phosphorus fractions in growers’ paddocks in the northern Victorian grain belt - D. T. Vu; R. D. Armstrong; P. J. Newton; C. Tang (Nutrient Cycling in Agroecosystems, 2011)

Phosphorus availability for three crop species as a function of soil type and fertilizer history - Dang T. Vu; Roger D. Armstrong; Peter W. G. Sale; Caixian Tang (Plant and Soil, 2010)

Phylogenetic analysis of bacterial communities in the shrimp and sea cucumber aquaculture environment in northern China by culturing and PCR–DGGE - Qiufen Li; Y. Zhang; D. Juck; N. Fortin; Charles W. Greer; Qisheng Tang (Aquaculture International, 2010)

Ecological Restoration of Polluted Plain Rivers Within the Haihe River Basin in China - W. Wang; X. Q. Tang; S. L. Huang; S. H. Zhang; C. Lin; D. W. Liu; H. J. Che; Q. Yang; Miklas Scholz (Water, Air, & Soil Pollution, 2010)

Application of nitrogen in NO 3 − form increases rhizosphere alkalisation in the subsurface soil layers in an acid soil - C. Weligama; C. Tang; P. W. G. Sale; M. K. Conyers; D. L. Liu (Plant and Soil, 2010)

A real‐time PCR for the detection of hepatopancreatic parvovirus (HPV) of penaeid shrimp - D C Yan; K F J Tang; D V Lightner (Journal of Fish Diseases, 2010)
Hepatopancreatic parvovirus (HPV) causes a common shrimp disease that occurs in many shrimp farming regions, especially in the Indo Pacific, and infects most of the cultured penaeid species. There are seven geographic HPV isolates known, so a method to detect different HPV types is needed. We developed a sensitive and generic real‐time PCR assay for the detection of HPV. A pair of primers and TaqMan probe based on an HPV sequence obtained from samples of Fenneropenaeus chinensis from Korea were selected, and they were used to amplify a 92 bp DNA fragment. This real‐time PCR was found to be specific to HPV and did not react with other shrimp viruses. A plasmid (pHPV‐2) containing the target HPV sequence was constructed and used for determination of the sensitivity of this assay. The assay could detect a single copy of plasmid DNA, and it was used successfully in finding HPV in shrimp samples from the China‐Yellow Sea region, Taiwan, Korea, Thailand, Madagascar, New Caledonia and Tanzania.

Recombinant respiratory syncytial virus F protein expression is hindered by inefficient nuclear export and mRNA processing - Kelly Huang; Heather Lawlor; Roderick Tang; Randall S. MacGill; Nancy D. Ulbrandt; Herren Wu (Virus Genes, 2010)

Nitrate leaching stimulates subsurface root growth of wheat and increases rhizosphere alkalisation in a highly acidic soil - C. Weligama; P. W. G. Sale; M. K. Conyers; D. L. Liu; C. Tang (Plant and Soil, 2010)

Development of a low-cost system for measuring conditional time-averaged gradients of SO2 and NH3 - D. Famulari; D. Fowler; E. Nemitz; K. J. Hargreaves; R. L. Storeton-West; G. Rutherford; Y. S. Tang; M. A. Sutton; K. J. Weston (Environmental Monitoring and Assessment, 2010)

Transformations and availability of phosphorus in three contrasting soil types from native and farming systems: A study using fractionation and isotopic labeling techniques - D. T. Vu; C. Tang; R. D. Armstrong (Journal of Soils and Sediments, 2010)

Distribution of pathogenic Yersinia enterocolitica in China - X. Wang; Z. Cui; D. Jin; L. Tang; S. Xia; H. Wang; Y. Xiao; H. Qiu; Q. Hao; B. Kan; J. Xu; H. Jing (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Central metabolism in Mycobacterium smegmatis during the transition from O2-rich to O2-poor conditions as studied by isotopomer-assisted metabolite analysis - Yinjie J. Tang; Wenqing Shui; Samuel Myers; Xueyang Feng; Carolyn Bertozzi; Jay D. Keasling (Biotechnology Letters, 2009)

Partial molecular cloning, characterization, and analysis of the subcellular localization and expression patterns of the porcine OTUB1 gene - T. L. Shan; Z. L. Tang; D. Z. Guo; S. L. Yang; Y. L. Mu; Y. H. Ma; W. J. Guan; K. Li (Molecular Biology Reports, 2009)

Comparison of Approaches to Calibrate a Surface Complexation Model for U(VI) Sorption to Weathered Saprolite - F. Zhang; J. C. Parker; S. C. Brooks; Y.-J. Kim; G. Tang; P. M. Jardine; D. B. Watson (Transport in Porous Media, 2009)

Construction, Characterization, and Expressed Sequence Tag (EST) Analysis of Normalized cDNA Library of Thermo-Photoperiod-Sensitive Genic Male Sterile (TPGMS) Wheat from Spike Developmental Stages - D. Yang; Z. H. Tang; L. P. Zhang; C. P. Zhao; Y. L. Zheng (Plant Molecular Biology Reporter, 2009)

Time-Dependent Oxidative Stress Responses of Crucian Carp (Carassius auratus) to Intraperitoneal Injection of Extracted Microcystins - X. Zhang; P. Xie; D. Li; R. Tang; H. Lei; Y. Zhao (Bulletin of Environmental Contamination and Toxicology, 2009)

Full-length coding sequences, polymorphism and chromosomal localizations of the porcine EDG4 and EDG7 genes - T. L. Shan; K. Li; Z. L. Tang; S. L. Yang; Y. H. Ma; W. J. Guan; D. Z. Guo (Molecular Biology Reports, 2009)

Bombyx mori nucleopolyhedrovirus ORF51 encodes a budded virus envelope associated protein - C.-H. Tian; X.-D. Tang; H.-J. Xu; J.-Q. Ge; Y.-G. Miao; C.-X. Zhang (Virus Genes, 2009)

Aflatoxin–albumin adducts and correlation with decreased serum levels of vitamins A and E in an adult Ghanaian population - L. Tang; L. Xu; E. Afriyie-Gyawu; W. Liu; P. Wang; Y. Tang; Z. Wang; H.J. Huebner; N.-A. Ankrah; D. Ofori-Adjei; J.H. Williams; J.-S. Wang; et al. (Food Additives & Contaminants: Part A, 2009)

Investigation of Impatiens necrotic spot virus outbreaks in New Zealand - D. R. Elliott; B. S. M. Lebas; F. M. Ochoa-Corona; J. Tang; B. J. R. Alexander (Australasian Plant Pathology, 2009)

Investigation of an outbreak of Soil-borne wheat mosaic virus in New Zealand - B. S. M. Lebas; F. M. Ochoa-Corona; D. R. Elliott; J. Tang; A. G. Blouin; O. E. Timudo; S. Ganev; B. J. R. Alexander (Australasian Plant Pathology, 2009)

Localised nitrate and phosphate application enhances root proliferation by wheat and maximises rhizosphere alkalisation in acid subsoil - C. Weligama; C. Tang; P. W. G. Sale; M. K. Conyers; D. L. Liu (Plant and Soil, 2008)

Near‐surface air temperature estimation from ASTER data based on neural network algorithm - K. B. Mao; H. J. Tang; X. F. Wang; Q. B. Zhou; D. L. Wang (International Journal of Remote Sensing, 2008)

Inhibition of the development of collagen-induced arthritis in Wistar rats through vagus nerve suspension: a 3-month observation - P. Zhang; D. Han; T. Tang; X. Zhang; K. Dai (Inflammation Research, 2008)

A method for retrieving soil moisture in Tibet region by utilizing microwave index from TRMM/TMI data - K. B. Mao; H. J. Tang; L. X. Zhang; M. C. Li; Y. Guo; D. Z. Zhao (International Journal of Remote Sensing, 2008)

Input–Output Budgets for Inorganic Nitrogen Under Acid Rain in a Subtropical Evergreen Mixed Forest in Central-South China - C. Y. Du; G. M. Zeng; G. Zhang; L. Tang; X. D. Li; D. L. Huang; L. Huang; Y. M. Jiang (Water, Air, & Soil Pollution, 2008)

Changes and availability of P fractions following 65 years of P application to a calcareous soil in a Mediterranean climate - D. T. Vu; C. Tang; R. D. Armstrong (Plant and Soil, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Comparison of four infectious bursal disease viruses isolated from different bird species - Y. S. Wang; Z. C. Wang; Y. D. Tang; Z. L. Shi; K. W. He; Y. Li; J. B. Hou; H. C. Yao; H. J. Fan; C. P. Lu (Archives of Virology, 2007)

Allomermis solenopsi n. sp. (Nematoda: Mermithidae) parasitising the fire ant Solenopsi s invicta Buren (Hymenoptera: Formicidae) in Argentina - George O. Poinar; Sanford D. Porter; Sha Tang; Bradley C. Hyman (Systematic Parasitology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Extraction of Trigonella foenum-graecum L. by supercritical fluid CO2 and its contact toxicity to Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) - G. W. Tang; C. J. Yang; L. D. Xie (Journal of Pest Science, 2007)

Multi‐sensor studies of the Sumatra earthquake and tsunami of 26 December 2004 - R. P. Singh; G. Cervone; M. Kafatos; A. K. Prasad; A. K. Sahoo; D. Sun; D. L. Tang; R. Yang (International Journal of Remote Sensing, 2007)

Phylogenetic utility of protein (RPB2, β-tubulin) and ribosomal (LSU, SSU) gene sequences in the systematics of Sordariomycetes (Ascomycota, Fungi) - Alvin M. C. Tang; Rajesh Jeewon; Kevin D. Hyde (Antonie van Leeuwenhoek, 2007)

Mitochondrial DNA phylogeny of two morphologically enigmatic fishes in the subfamily Schizothoracinae (Teleostei: Cyprinidae) in the Qinghai‐Tibetan Plateau - D. Qi; S. Guo; J. Tang; X. Zhao; J. Liu (Journal of Fish Biology, 2007)
The complete mitochondrial DNA (mtDNA) cytochrome b gene (1140 bp) was sequenced in Herzenstein macrocephalus and Gymnocypris namensis and in 13 other species and sub‐species ( n = 22), representing four closely related genera in the subfamily Schizothoracinae. Conflicting taxonomies of H. macrocephalus and G. namensis have been proposed because of the character instability among individuals. Parsimony, maximum likelihood and Bayesian methods produced phylogenetic trees with the same topology and resolved several distinctive clades. Previous taxonomic treatments, which variously placed these two species of separate genera or as sub‐species, are inconsistent with the mtDNA phylogeny. Both H. macrocephalus and G. namensis appear in a well‐supported clade, which also includes nine species of Schizopygopsis , and hence should be transferred to the genus Schizopygopsis . Morphological changes are further illustrated, and their adaptive evolution in response to the local habitat shifts during the speciation process appears to be responsible for conflicting views on the systematics of these two species and hence the contrasting taxonomic treatments. These species are endemic to the Qinghai‐Tibetan Plateau, a region with a history of geological activity and a rich diversity of habitats that may have result in the parallel and reversal evolution of some morphological characters used in their taxonomies. Our results further suggest that speciation and morphological evolution of fishes in this region may be more complex than those previously expected.

Upregulation of leptin pathway correlates with abnormal expression of SERCA2a, phospholamban and the endothelin pathway in heart failure and reversal by CPU86017 - T. Na; D. Z. Dai; X. Y. Tang; Y. Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Molecular and cytogenetic characterization of an Oryza officinalis–O. sativa chromosome 4 addition line and its progenies - Huajun Jin; Guangxuan Tan; D. S. Brar; Ming Tang; Gang Li; Lili Zhu; Guangcun He (Plant Molecular Biology, 2006)

Genome-wide linkage scans for loci affecting total cholesterol, HDL-C, and triglycerides: the Family Blood Pressure Program - Suzette J. Bielinski; Weihong Tang; James S. Pankow; Michael B. Miller; Thomas H. Mosley; Eric Boerwinkle; Richard A. Olshen; J. David Curb; Cashell E. Jaquish; D. C. Rao; Alan Weder; Donna K. Arnett (Human Genetics, 2006)

Identifying Potential Conflict Associated with Oil and Gas Exploration in Texas State Coastal Waters: A Multicriteria Spatial Analysis - Samuel D. Brody; Himanshu Grover; Sarah Bernhardt; Zhenghong Tang; Bianca Whitaker; Colin Spence (Environmental Management, 2006)

Racial admixture and its impact on BMI and blood pressure in African and Mexican Americans - Hua Tang; Eric Jorgenson; Maya Gadde; Sharon L. R. Kardia; D. C. Rao; Xiaofeng Zhu; Nicholas J. Schork; Craig L. Hanis; Neil Risch (Human Genetics, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Local Maximal Stress Hypothesis and Computational Plaque Vulnerability Index for Atherosclerotic Plaque Assessment - Dalin Tang; Chun Yang; Jie Zheng; Pamela K. Woodard; Jeffrey E. Saffitz; Joseph D. Petruccelli; Gregorio A. Sicard; Chun Yuan (Annals of Biomedical Engineering, 2005)

Firing rates of pallidal neurons are similar in Huntington’s and Parkinson’s disease patients - Joyce K. H. Tang; Elena Moro; Andres M. Lozano; Anthony E. Lang; William D. Hutchison; Neil Mahant; Jonathan O. Dostrovsky (Experimental Brain Research, 2005)

PAQR Proteins: A Novel Membrane Receptor Family Defined by an Ancient7-Transmembrane Pass Motif - Y. Tom Tang; Tianhua Hu; Matthew Arterburn; Bryan Boyle; Jessica M. Bright; Peter C. Emtage; Walter D. Funk (Journal of Molecular Evolution, 2005)

Tree photosynthesis modulates soil respiration on a diurnal time scale - Jianwu Tang; Dennis D. Baldocchi; Liukang Xu (Global Change Biology, 2005)
To estimate how tree photosynthesis modulates soil respiration, we simultaneously and continuously measured soil respiration and canopy photosynthesis over an oak‐grass savanna during the summer, when the annual grass between trees was dead. Soil respiration measured under a tree crown reflected the sum of rhizosphere respiration and heterotrophic respiration; soil respiration measured in an open area represented heterotrophic respiration. Soil respiration was measured using solid‐state CO 2 sensors buried in soils and the flux‐gradient method. Canopy photosynthesis was obtained from overstory and understory flux measurements using the eddy covariance method. We found that the diurnal pattern of soil respiration in the open was driven by soil temperature, while soil respiration under the tree was decoupled with soil temperature. Although soil moisture controlled the seasonal pattern of soil respiration, it did not influence the diurnal pattern of soil respiration. Soil respiration under the tree controlled by the root component was strongly correlated with tree photosynthesis, but with a time lag of 7–12 h. These results indicate that photosynthesis drives soil respiration in addition to soil temperature and moisture.

The persistence of ripe fleshy fruits in the presence and absence of frugivores - Alvin M. C. Tang; Richard T. Corlett; Kevin D. Hyde (Oecologia, 2005)

Distribution of Potato spindle tuber viroid in New Zealand glasshouse crops of capsicum and tomato - B. S. M. Lebas; G. R. G. Clover; F. M. Ochoa-Corona; D. R. Elliott; Z. Tang; B. J. R. Alexander (Australasian Plant Pathology, 2005)

The Fed-1 (CAUU)4 element is a 5? UTR dark-responsive mRNA instability element that functions independently of dark-induced polyribosome dissociation - Sumana Bhat; Li Tang; Angela D. Krueger; Christopher L. Smith; Sharon R. Ford; Lynn F. Dickey; Marie E. Petracek (Plant Molecular Biology, 2004)

Inheritance of early elongation ability in floating rice revealed by diallel and QTL analyses - K. Nemoto; Y. Ukai; D.-Q. Tang; Y. Kasai; M. Morita (Theoretical and Applied Genetics, 2004)

All Roads Lead to Arginine: The Squid Protamine Gene - John D. Lewis; Miriam E. de Jong; Sabira M. Bagha; Alpina Tang; William F. Gilly; Juan Ausió (Journal of Molecular Evolution, 2004)

Heart-type fatty acid binding proteins are upregulated during terminal differentiation of mouse cardiomyocytes, as revealed by proteomic analysis - M. K. Tang; P. M. Kindler; D. Q. Cai; P. H. Chow; M. Li; K. K. H. Lee (Cell and Tissue Research, 2004)

Evaluation of an Immortalized Retinal Endothelial Cell Line as an In Vitro Model for Drug Transport Studies Across the Blood-Retinal Barrier - Jie Shen; Stacy T. Cross; Diane D. S. Tang-Liu; Devin F. Welty (Pharmaceutical Research, 2003)

Modelling the distribution, sustainability and diapause emergence timing of the copepod Calanus finmarchicus in the Labrador Sea - D. P. Tittensor; B. DeYoung; C. L. Tang (Fisheries Oceanography, 2003)
It is now recognized that Calanus finmarchicus , the dominant copepod zooplankter of the North Atlantic, has most of its biomass in the open ocean. While the Labrador Sea does contain a large population of Calanus finmarchicus , the importance of possible connections with the rest of the North Atlantic are not understood. Although there are few wintertime observations, sufficient data exist to model the role of the circulation, temperature and food supply on population dynamics. This study couples a biological model of Calanus finmarchicus with a physical oceanographic model of the Labrador Sea, using chlorophyll data derived from observations by the satellite‐borne SeaWiFS (Sea‐viewing Wide Field‐of‐view Sensor) as a proxy food supply for the numerical copepods. We produce a large‐scale, comprehensive picture of the spatial distribution of Calanus finmarchicus in the Labrador Sea, along with an exploration of the timing of diapause and an examination of population sustainability. We are able to simulate reasonably well the temporal and spatial patterns of Calanus finmarchicus in the Labrador Sea. During a year long model run, the population has a single generation over most of the Labrador Sea, with a final diapausing population about 50% the size of the initial for the parameters used in these simulations. A latitudinally dependent diapause emergence scheme with early emergence to the south of Newfoundland provides the best fit to data. A change of 0.5°C in the temperature field can cause significant changes in the population abundance in a single year, due to changes in Calanus finmarchicus growth rates.

Amplification of badnavirus-like sequences from Yucca elephantipes - G. R. G. Clover; M. N. Pearson; D. R. Elliott; Z. Tang; T. E. Smales; B. J. R. Alexander (Australasian Plant Pathology, 2003)

Recombinant adenovirus encoding the HA gene from swine H3N2 influenza virus partially protects mice from challenge with heterologous virus: A/HK/1/68 (H3N2) - M. Tang; J. A. Harp; R. D. Wesley (Archives of Virology, 2002)

Screening rough-seeded lupins (Lupinus pilosus Murr. and Lupinus atlanticus Glads.) for tolerance to calcareous soils - J. D. Brand; C. Tang; A. J. Rathjen (Plant and Soil, 2002)

Erratum to: Building a mouse model hallmarking the congenital human cytomegalovirus infection in central nervous system - J. L. Tang; M. L. Wang; J. J. Qiu; D. Wu; W. Hu; B. F. Shi; Y. Hu; J. P. Li (Archives of Virology, 2002)

Building a mouse model hallmarking the congenital human cytomegalovirus infection in central nervous system - J. Tang; M. Wang; J. Qiu; D. Wu; W. Hu; B. Shi; Y. Hu; J. Li (Archives of Virology, 2002)

Development and mapping of AFLP markers linked to the sorghum fertility restorer gene rf4 - L. Wen; H. V. Tang; W. Chen; R. Chang; D. R. Pring; P. E. Klein; K. L. Childs; R. R. Klein (Theoretical and Applied Genetics, 2002)

Integrated Monitoring Program on Acidification of Chinese Terrestrial Systems (Impacts) — A Chinese-Norwegian Cooperation Project - D. Tang; E. Lydersen; H. M. Seip; V. Angell; O. Eilertsen; T. Larssen; X. Liu; G. Kong; J. Mulder; A. Semb; S. Solberg; K. Torseth; et al. (Water, Air, & Soil Pollution, 2001)

Comparison of the Effects of Wet N Deposition (NH4Cl) and Dry N Deposition (NH3) on UK Moorland Species - Ian D. Leith; Lucy J. Sheppard; Carole E.R. Pitcairn; J. Neil Cape; Paul W. Hill; Valerie H. Kennedy; Y. Sim Tang; Ron I. Smith; David Fowler (Water, Air, & Soil Pollution, 2001)

A simple and rapid procedure to establish embryogenic cell suspensions as a source of protoplasts for efficient plant regeneration from two Chinese commercial rice cultivars - K. Tang; X. Sun; D. An; J. B. Power; E. C. Cocking; M. R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Cultivar variation in the effect of chlorsulfuron in depressing the uptake of copper in wheat - C. Tang; A. D. Robson (Plant and Soil, 2000)

Mapping of QTLs conferring resistance to bacterial leaf streak in rice - D. Tang; W. Wu; W. Li; H. Lu; A. J. Worland (Theoretical and Applied Genetics, 2000)

Regulation of body dimethylsulfoniopropionate (DMSP) content by the copepod Temora longicornis : a test of four mechanisms - K. W. Tang; T. D. Fenn; P. T. Visscher; H. G. Dam (Marine Biology, 2000)

Plant regeneration from protoplasts of a commercial Asian long-grain javanica rice - K. Tang; X. Sun; D. An; J.B. Power; E.C. Cocking; M.R. Davey (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Geochemistry of HCO3 − at the sediment-water interface of lakes from the Southwestern Chinese plateau - F. C. Wu; H. R. Qing; G. J. Wan; D. G. Tang; R. G. Huang; Y. R. Cal (Water, Air, & Soil Pollution, 1997)

Differential Toxicity of Atrazine to Selected Freshwater Algae - J.-X. Tang; K. D. Hoagland; B. D. Siegfried (Bulletin of Environmental Contamination and Toxicology, 1997)

Anxiolytic-like effects of PNU-101017, a partial agonist at the benzodiazepine receptor - A. H. Tang; S. R. Franklin; D. B. Carter; V. H. Sethy; L. M. Needham; E. J. Jacobsen; P. F. Von Voigtlander (Psychopharmacology, 1997)

Electron microscopic evidence for the association of M 2 protein with the influenza virion - D. C. Jackson; Xi-Lin Tang; K. Gopal Murti; R. G. Webster; G. W. Tregear; W. J. Bean (Archives of Virology, 1991)